2021
DOI: 10.1021/acs.est.1c02381
|View full text |Cite
|
Sign up to set email alerts
|

In-Furnace Control of Arsenic Vapor Emissions Using Fe2O3 Microspheres with Good Sintering Resistance

Abstract: The addition of Fe2O3 into furnaces is a promising method for arsenic pollution control. Nevertheless, Fe2O3 particles undergo serious sintering under actual furnace temperatures. To improve its sintering resistance, Fe2O3 hollow microspheres were synthesized by the template method and were tested in flue gas containing SO2 and NO in the range of 1000–1300 °C. The results demonstrated that the amount of arsenic captured could be steadily maintained above 5 mg/g throughout the operating temperature range, and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…To further explain this phenomenon, FT-IR was carried out to study the changes of active functional groups on the surface of sorbent before and after the reaction. As shown in Figure , when SO 2 was introduced into the reaction, the new characteristic peak appeared at about 1160 cm –1 , which could be attributed to HSO 4 – or SO 4 2– . , SO 2 was converted to SO 3 under the catalytic oxidation of α-Fe 2 O 3 . Subsequently, under the action of water vapor, SO 3 was attached to the surface or pores of the sorbent in the form of HSO 4 – /SO 4 2– .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To further explain this phenomenon, FT-IR was carried out to study the changes of active functional groups on the surface of sorbent before and after the reaction. As shown in Figure , when SO 2 was introduced into the reaction, the new characteristic peak appeared at about 1160 cm –1 , which could be attributed to HSO 4 – or SO 4 2– . , SO 2 was converted to SO 3 under the catalytic oxidation of α-Fe 2 O 3 . Subsequently, under the action of water vapor, SO 3 was attached to the surface or pores of the sorbent in the form of HSO 4 – /SO 4 2– .…”
Section: Resultsmentioning
confidence: 93%
“…NO has little effect on adsorption performance, far less obvious than SO 2 . The role of O 2 is closely related to the adsorption process, and the lattice oxygen and chemisorbed oxygen are the main factors affecting the migration and adsorption capacity of gas-phase arsenic …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the minor peak at around 732.2 eV suggests that a little Fe 3+ was reduced to Fe 2+ along with the oxidation of Co 2+ to Co 3+ [19][20][21][22][23]. SEM images of the CF heterostructure are shown in Figure 2a-c.…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that Fe 3+ ions were still dominant, which corresponded to the Fe 2 O 3 phase. However, the minor peak at around 732.2 eV suggests that a little Fe 3+ was reduced to Fe 2+ along with the oxidation of Co 2+ to Co 3+ [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%